A educação física e o esporte no estado de Mato Grosso : uma odisseia biográfica do professor João Batista Jaudy - Ferreira, Talita (2015)
The biography is a known history genre, however, this is approaching subtly Physical Education through narratives produced in the area seeking to positively highlight the work of some teachers and / or athletes for their achievements and sporting glories. Thus, in order to broaden the study of the biographical genre in Physical Education, is aimed, from this research, display and analysis of the trajectory of Professor João Batista Jaudy (* 1934 † 2009) in the context of Physical Education and Sport in state of Mato Grosso, with a view to highlighting the actions undertaken in pursuit of Physical Education and Sport, which will give it the nickname "precursor" before this context. Initially, a major concern was to estimate the historical and scientific value to the biography of Professor Professor João Batista Jaudy, seeing this, the great supporter of a project that took place: the creation of the first course in Physical Education Mato Grosso State.We risk studying a trajectory of remembering and "count" of a group of subjects, previously defined, in order to understand the complex web of relationships on which were inscribed the individuals who formed the investigative space biography in this project: the Faculty of Physical Education (FEF) of the Federal University of Mato Grosso (UFMT). Methodologically considering the biographical argumentative character, appealed to both oral sources derived from the narratives generated by interviews with employees who permeated at some point for the life of Professor João Batista Jaudy, the documents printed, audiovisual, iconographic, and others who have made mention of it and his involvement with the course of Physical Education and sport in Mato Grosso. From the subjectivity that permeates the research fieldwork, we obtained as important facts results of an individual story that was built in the collective from multiple perspectives, interests and points of view, promoting the history excluded the official story, and constituent part of the institutional collection of the FEF / UFMT. The results also allowed the reconstruction of historical and cultural journey of a certain group and institution - which is a social field this research - thus explaining the representation of biography and its importance in the history of sport and physical education in the state of Mato Grosso .